2008
DOI: 10.2527/jas.2007-0175
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in Colombian Creole cattle populations estimated by pedigree information1

Abstract: Genetic parameters for cattle's growth characteristics were estimated in Romosinuano creole breed cattle forming part of the Turipaná research centre's conservation program , located in the Valle del Sinú (Córdoba, Colombia). A univariate animal model was used for production characteristics such as birth weight (BW), weaning weight (WW, adjusted at 270 days), 16-month weight (16m W), daily weaning weight gain (DWWG) and daily weight gain at 16 months (DWG16m). Mean heritability values were 0.28, 0.43 and 0.38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 34 publications
(37 reference statements)
3
21
1
10
Order By: Relevance
“…of animals Animals with PEC>0.8 a Six of these were also used in herd A b Three of these were also used in herd A 2001) and Caracu in Brazil (Pereira et al 2005) than those we detected in the Reyna Creole cattle. Some information is also available for Limonero Creole cattle in Venezuela (Villasmil-Ontiveros et al 2008) and for Romosinuano, Sanmartinero, Costeño con Cuernos, and Blanco Orejinegro breeds in Colombia (Martinez et al 2008). The proportion of inbred animals in each case and the highest F x values were all lower than those found in our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…of animals Animals with PEC>0.8 a Six of these were also used in herd A b Three of these were also used in herd A 2001) and Caracu in Brazil (Pereira et al 2005) than those we detected in the Reyna Creole cattle. Some information is also available for Limonero Creole cattle in Venezuela (Villasmil-Ontiveros et al 2008) and for Romosinuano, Sanmartinero, Costeño con Cuernos, and Blanco Orejinegro breeds in Colombia (Martinez et al 2008). The proportion of inbred animals in each case and the highest F x values were all lower than those found in our study.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, some sires and dams have been quite old when they produced bulls, which contributed to increased generation intervals. These factors are likely to have had mixed effects on conservation prospects, since opportunities for genetic improvement are reduced by prolonged generation intervals, but losses of genetic variability per unit time may also be reduced (Martinez et al 2008). Creole cattle are generally expected to maintain production and reproduction under dry, tropical conditions where other cattle may not survive (Russell et al 2000), but whether this applies to Reyna Creole cattle needs to be confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…; Martínez et al . ). Two tropically adapted Creole breeds and their likely Spanish ancestors were analysed to establish epigenomic differences among groups accounting for breed similarities related to their geographical location.…”
Section: Discussionmentioning
confidence: 97%
“…These methods have provided significant insights into the genetic structure of economically important species. Despite these advances there is still a need for information about pedigree in order to identify temporal trends and to evaluate inbreeding, confirmation of pedigree, effective size, generation interval, genetic diversity and several other important population parameters (FARIA et al, 2004;CARNEIRO et al 2009;MALHADO et al, 2008a,b;MARTÍNEZ et al, 2008). Studies utilizing historical pedigree records can identify and uncover important circumstances that have influenced the genetic history of a population (VALERA et al, 2005), moreover, some population parameters that are strongly dependent on management and mating systems have significant impacts on genetic variability.…”
Section: Introductionmentioning
confidence: 99%